Lipid droplets and fatty acid‐induced lipotoxicity: in a nutshell - Obaseki, Eseiwi; Adebayo, Daniel; Bandyopadhyay, Sumit; Hariri, Hanaa (FEBS letters, 2024)
Lipid droplets (LDs) are fat storage organelles that are conserved from bacteria to humans. LDs are broken down to supply cells with fatty acids (FAs) that can be used as an energy source or membrane synthesis. An overload of FAs disrupts cellular functions and causes lipotoxicity. Thus, by acting as hubs for storing excess fat, LDs prevent lipotoxicity and preserve cellular homeostasis. LD synthesis and turnover have to be precisely regulated to maintain a balanced lipid distribution and allow for cellular adaptation during stress. Here, we discuss how prolonged exposure to excess lipids affects cellular functions, and the roles of LDs in buffering cellular stress focusing on lipotoxicity. Fatty acids (FAs) are critical molecules for cell growth, proliferation, and development; but are toxic to cells when present in excess. Eukaryotic cells therefore sequester FAs in organelles called lipid droplets (LDs) until needed. LD synthesis and breakdown are under precise metabolic control, and dysregulation of these pathways is linked to lipotoxicity and diseases.